MAGNETIC SUSCEPTIBILITY OF SOIL AND ITS SIGNIFICANCE IN EROSION STUDIES - Kruglov О.; Menshov О.; Nazarok, P.; Kolada, L.; Kolada, V.; Achasova А. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Water erosion of the soil is a major factor in the degradation of agricultural land in Ukraine. About 13 million hectares of arable land need additional protection. The study of the influence of the mentioned hazard processes is important both for the scientists and land endusers. The purpose of the paper is to demonstrate the possibilities of soil magnetic susceptibility mapping in erosion studies. The comparison with traditional methods is implemented. The studies were carried out at the territory of Farm Enterprise "Phoenix" of the Bliznyukovsky district of the Kharkiv region at the distance of 6 km to the southeast of the Lozova. The study site is used for crop production. The relief of the site is complicated by the developed ravine network. The soil is ordinary chernozems (Haplic Chernozems in WRB classification). We have registered high correlation between magnetic susceptibility (MS) of the studied chernozems and humus content (organic matter). The Spearman correlation coefficient slightly depends on the frequency magnetic susceptibility coefficient. The results give the opportunity to recommend soil MS studies as the additional tool in soil erosion mapping. The magnetic measurements are expensive and fast for the humus (organic matter) identification of eroded soil. The relation of the values of soil MS and the value of potential soil loss at the studied area was low. The study of the magnetic mineralogy confirmed the absence of the anthropogenic soil pollution. We confirmed this by the values of the frequency dependence of magnetic susceptibility which were above 6. The domination of the superparamagnetic (SP) grains with the size less than 20 nm was confirmed by the values of the frequency dependence of magnetic too. The majority of the MS values are 10-20. The magnetic minerals of the studied soil have been formed in real time under the pedogenic (natural soil formation) process.